EFFECTIVE POSSESSION AND IMPROVEMENT OF «SOFT SKILLS» IN THE CONTINUOUS DEVELOPMENT CONTEXT OF TEACHERS’ PROFESSIONAL COMPETENCE (Innovative professional education, 2024)
The article presents theoretical and practical aspects of the problem of forming «soft skills» in teachers and students of Professional Pre-Higher Education. Examples of their formation by means of intercultural communication, development and implementation of social projects, continuous development of the teachers’ professional competence are given.
Keywords: research, soft skills, educational environment, project work, professional development